Is Exclusive Breastfeeding a Protective Factor for Childhood Asthma and Eczema? - Liota, Andrea; Teouri, Ruth; Wong, Janice (Université d'Ottawa | University of Ottawa, 2017)
Background: There is much controversy on the benefits and disadvantages of breastfeeding, yet research is progressing to provide clarity on these inconsistencies. Evidence from research is still unclear as to whether breastfeeding will benefit childhood asthma and/or eczema by lowering the risks of it in babies, which could also lead to a positive outcome as they age, compared to different milk formulas. Objective: The aim of this literature review is to investigate if exclusive breastfeeding for at least three months is protective against childhood asthma and/or eczema in children ages 0 to 18 years, when compared to those who were not exclusively breastfed for at least three months. Methods: A structured literature review was conducted on published studies using the terms "breastfeeding" AND "asthma and Eczema", "exclusive breastfeeding" AND "asthma and Eczema" in uOttawa Search+, PubMed, and Scholar’s Portal. Search results were refined according to inclusion and exclusion criteria. These refined results yielded 9 relevant articles for further examination. Results: The research strategy allowed for 9 articles to be included for review, with various study designs. In general, the results were too varied for a consensus to be made. 3 studies showed a negative association and 3 showed positive for the eczema outcome, 4 showed a positive association for asthma and 3 showed no effect on either. Conclusion: Variations and incongruences in the research make it difficult to conclude for certain a significant association. More research needs to be performed in order to establish a well-defined relationship generalizable to a local population.